CRITICAL THINKING: DILIHAT DARI PERSEPSI DOSEN BAHASA INGGRIS PADA PRESENTASI DAN DISKUSI MAHASISWA - Mayuasti, Mayuasti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Presentation and discussion are strategies that are applied by lecturers in the learning process. The strategies give a big opportunity to the students exploring and expanding logical and critical ideas. It is indicated that managing critical thinking during presentation and discussion is needed. Hence, this research focuses on investigating the lecturers’ perception to the integration of critical thinking in students’ presentation and discussion. It is survey research. The technique in determining sample is purposive. Moreover, the instrument used is the questionnaire. The result of the data is analyzed by statistic formula. The analysis of the data exposes lecturers’ perception of critical thinking in students’ presentation and discussion. The results shows that lecturers have positive perception to critical thinking in the students’ presentation and discussion.